nv98i3hx6u
nv98i3hx6u
17-08-2021
Mathematics
contestada
If a = b then a - c = b - c
Respuesta :
aniilsah555
aniilsah555
17-08-2021
Step-by-step explanation:
Solution,
Given:-a=b
Now,
a-c=b-c
Then,
a-c=a-c ,because a=b is given
Again,
a-c-(a-c)=0
a-c-a+c=0
0=0
At last,
0 will be the answer.
Stay safe, stay happy
Answer Link
VER TODAS LAS RESPUESTAS ( 66+ )
Otras preguntas
Kjeldahl's method can be used in the estimation of __________
Graph the points ( – 1.5,4.5) and ( – 3.5,3.5) on the coordinate plane.
A delivery truck is transporting boxes of two sizes: large and small. The combined weight of a large box and a small box is 70 The truck is transporting 60 larg
what materials you would set out in a four-surface amalgam procedure?
How did the south African government respond to the ANC meeting
The College Board estimated the mean SAT score in 2016 was 1083 points with a standard deviation of 193 points. Assume the distribution of SAT scores is unknown
Help with graphing rational functions
If a gas is initially at a pressure of 1.56 atm and has a volume of 556 mL, what is the pressure if the balloon is compressed to a volume of 224 mL
8 apples cost $1.44 how mucho is 1 cost
What is Mr. Smith's dog name
ACCESS MORE